Modern Technologies for Introducing Preschool Children to Works of Literature (Eurasian Journal of Learning and Academic Teaching, 2023)
This article modern technologies for introducing preschool children to works of literature and also gives recommendations on the development of children's speech through the leading methods of introducing them to literature